Sports Coaches Managerial Competences: A Major Factor for Success in Inter-University Games - ALUYA, Christopher Osas (Ilorin Journal of Education, 2024)
This paper reviewed the coaching competences of sports coaches engaged in Universities in Nigeria with special interest in Universities in Edo state on how they can achieve success in the sports performance outcome of student-athletes in these universities. Also, the role of sports coaches, sports coaches’ coaching competences as well as student-athletes sports participation in universities in Nigeria were reviewed and discussed. Thereafter, the recommendations were that when there is effective sports administration, sports administrators would map out activities to be performed by coaches. They will put machineries together to get the activities done and hire qualified, competent and capable coaches to carry out the activities. In doing these, tasks will be distributed accordingly with corresponding authority. There will be harmonization of the activities of all the coaches and departments and ways to bring about and expand revenue for the success of the organization will be fashioned out. When all these are put in place, effective sports administration in the Universities would naturally bring about improvement and success in university sports.